Contextually Relevant Teaching of the Composition of the Torah - Reed, Justin (Teaching theology and religion, 2025)
This essay summarizes teaching goals when the content is theories of biblical composition and the context is a liberal/progressive classroom of first-year seminary students. For teaching to be relevant to this group and responsible in the world, the professor explains four main strategies or learning goals that guide the class away from memorization of complex models and toward considerations that will most likely be useful for students' vocational contexts. These four foci are (1) developing greater comfort with historical criticism; (2) emphasizing the evidence that scholars engage with more than the overarching theories; (3) making space for classroom reflection on the implications of potentially challenging insights; and (4) filtering the entire learning experience through learning about hermeneutics.